Improving Green Entrepreneurial Knowledge, Motivation And Intention, And Identifying Barriers And Opportunities Of Adoption In Tayu Tea Community - Rini, Lamia Eva; Sahputri, Rindi Ardika Melsalasa; Siahaan, Limartaida; Setiawan, Gustap; Geby, Geby (UNIVED Press, 2026)
The study aims to investigate the impact of education and training program to improve green entrepreneurial knowledge, ecological awareness, green entpreneurial motivation and intention in Tayu tea community (farmers and entrepreneurs) in Bangka region. A mixed-method approach was used, combining pretest, posttest analysis and focus group discussion to explore primary barriers and opportunities in green entrepreneurship adoption. The paired t-test and wilcoxon signed-rank test were used to analyse the mean difference of pre- and posttest. Thematic analysis was used to analyse the focus group discussion result in the second step. The result found that there is a significant improvement of the green entrepreunial knowledge, awareness, motivation and intention after the intervention. The obstacles and opportunities to adaptation have also been identified in this paper. This study elucidates the necessary resources, identifies barriers to be overcome, and highlights potential opportunities that may facilitate successful adoption.